Effect of Methyltrienolone on the Metabolic Disorders in Rat Model of Alloxan-Induced Diabetes - MBiol, Neli Didebulidze; Kandelaki, Sopiko; Kakabadze, Manana; Kordzaia, Salome; Kordzaia, Dimitri; Relat, Jordi Muntané; Padillo, Javier (European Scientific Journal, ESJ, 2017)
Aim: The aim of the study was to investigate the restoration of metabolic imbalance related with deficiency of insulin by the exogenous androgen supplementation in the experimental model of alloxan-induced diabetes in Wistar male rats. Methods: The experimental diabetes was induced by a single intraperitoneal administration of alloxan. The concentrations of glucose, immunereactive insulin, corticosterone, testosterone and estradiol were examined in blood, the intensity of DNA and RNA synthesis and androgen receptor expression were studied in the liver tissue – at 15th, 30th and 45th days of alloxan-induced diabetes. The synthetic androgen methyltrienolone was administered to rats with 30-days diabetes during 15 days. All data were compared to control group received solvent. Results: The induction of diabetes increased the concentrations of glucose, corticosterone and estradiol while decreases insulin and testosterone concentration in blood as well as DNA/RNA synthesis and androgen receptors expression in hepatocytes. The administration of exogenous androgen significantly restored the metabolic imbalance and the expression of androgen receptors and increased DNA/RNA synthesis in liver cells maintained close to control level. Conclusion: The administration of methyltrienolone reduced the effect of “diabetic stress” and restored the hormonal dysfunction induced by alloxan.